Ontology-based Approach for Laptop Semantic Knowledge Representation - Yowe, Samson Cornelius Gele; Astawa, I Gede Santi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 4 (2021): JELIKU Volume 9 No 4, Mei 2021DO - 10.24843/JLK.2021.v09.i04.p05, 2021)
The rapid development of technology requires everyone to adapt. It is the same as the demands of work and school so that everyone should be more able to handle this problem. It is inevitable that the use of laptops today is not something that is a step. Almost all age groups use laptops to do school work, complete office work, or as a medium of entertainment. With so many types of laptops, some people are confused about choosing a laptop. The use of ontology as an information representation technique is a solution to this problem. Ontology can present information or knowledge sources semantically and organize various information resources in a systematic and structured manner. In the development of this ontology will be made using the methontology method. Methontology is one of the ontology model development methodologies which has advantages related to a detailed description of each activity. In addition, methontology also has other advantages, namely the development of ontology that are now made usable for further system development. Therefore, this study is proposed to build an ontology model that represents knowledge about laptops.